1990
DOI: 10.1021/ac00222a010
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of underivatized lipid biomarkers from microorganisms with pyrolysis short-column gas chromatography/ion trap mass spectrometry

Abstract: A microvolume Curie-point pyrolysis short-column (5 m) gas chromatography/mass spectrometry (Py-GC/MS) procedure was developed for the characterization of various lipid moieties in microorganisms. High linear flow rates (approximately 175 cm/s) characterized the GC conditions in order to effect an efficient chromatographic transfer and elution of the underivatized diglycerides and monoglycerides, and small modifications were necessary to the ion trap MS system in order for it to accommodate the relatively high… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
22
0

Year Published

1991
1991
2019
2019

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(24 citation statements)
references
References 48 publications
2
22
0
Order By: Relevance
“…As might be expected, there is a trend towards greater discriminating power as the analytical technique goes from a single component system such as GC to a multicotaponent Py-GC-MS or Py-MS-MS system. This is illustrated in the data analysis performed in the Py-GC-MS study 3 where several layers of information are present in the dataset. Major differences between bacterial species were readily apparent by visual inspection of the total ion current (TIC), whilst more subtle differences required analysis of the reconstructed ion chromatograms (RICs) and of individual GC-MS mass spectra.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…As might be expected, there is a trend towards greater discriminating power as the analytical technique goes from a single component system such as GC to a multicotaponent Py-GC-MS or Py-MS-MS system. This is illustrated in the data analysis performed in the Py-GC-MS study 3 where several layers of information are present in the dataset. Major differences between bacterial species were readily apparent by visual inspection of the total ion current (TIC), whilst more subtle differences required analysis of the reconstructed ion chromatograms (RICs) and of individual GC-MS mass spectra.…”
Section: Resultsmentioning
confidence: 99%
“…This is the basis of the fatty acid methyl ester (FAME) approach, which has been used successfully to characterize milligram amounts of bacteria through the saponification, derivatization and extraction of the lipid material to yield the methyl esters of the fatty acids which are then analyzed by gas chromatography 2 . The utility of this approach has been extended by the use of pyrolysis as a sample introduction technique, eliminating the need for time consuming extractions and derivatizations 3 .…”
Section: Introductionmentioning
confidence: 99%
“…However, these materials often yield volatile, gas chromatographable products upon controlled thermal degradation induced by pyrolysis (Anhalt et al, 1975;Gutteridge et al, 1987;Yang et al, 2003). These volatile components characterized by Py/MS or Py/GC/MS may then serve as fingerprints for classifying or studying the composition of different species of macromolecules (Snyder et al, 1990;Goodacre et al, 1991;DeLuca et al, 1993;Smith et al, 1993). In general, the pyrolysis of a complicated mixture like crude oil produces a wide variety of chemical compounds ranging in polarity from non-polar to highly polar.…”
Section: Conventional Analytical Approaches For Characterizing Polar mentioning
confidence: 99%
“…et al using the pyrolysis GC/ion trap detector system which showed maximum peaks at m/z 299 and 522 for E. coli (4).…”
Section: A Relatively Slow Programning Of 40mentioning
confidence: 99%
“…Forensic science and food industry applications developed following the pyrolysis fragmentation/chromatography research that provided informative "pyrograirs." Pyrolysis mass spectrometry (Py-MS) and pyrolysis GC-MS applications are now extended from the recent reports by Voorhees et al (3) and Snyder et al (4). Voorhees et al showed that Curie point pyrolysis-MS could provide fatty acid fragments from whole microorganisms that were informative for identification purposes.…”
mentioning
confidence: 99%